MENINGKATKAN KEAKTIFAN DAN HASIL BELAJAR MATERI SISTEM STATER PADA MATA PELAJARAN PEMELIHARAAN KELISTRIKAN KENDARAAN RINGAN DENGAN METODE PENEMUAN TERBIMBING PADA SISWA KELAS XI TKR SMK TAMANSISWA JETIS TAHUN PELAJARAN 2015/2016 - Dodi Setiawan; Suparmin Suparmin (Jurnal Taman Vokasi, 2016)
The purpose of this research for increase activities and result study of XI TKR B students of Vocational High School Tamansiswa academic year 2015/2016 in electrical light vehicle. Type of this research is action research class, subject of this research is XI TKR B students amount 25 students and the object is increase activities and result of study in electrical light vehicle using guided discovery method. Data accumulator technique in this research using observation, interview, test, and documentation. Data analysis technique about students doing observation during learning activity, while the result of study conduct by calculating the average value and percentage that completed KKM. Result of this research showing after using guided discovery method, activeness and result of student learning increase. It can be seen pra-cycle condition students activeness percentage 44,8%, cycle I percentage of students of activity 62%, cycle II percentage of students activity 70,8%, cycle III percentage of students activity 83,6%, while students average value before activity 64,40 with percentage of completeness about 33,33%, cycle I student average score 7,04 with percentage of completeness about 76%, cycle II students average before increased to 7,56 with percentage of completeness about 88% and cycle III students average score increased to 7,84 with percentage of completeness about 96%.